Ethical-legal issues regarding public vaccination - Cuadros Aguilera, Pol (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
Despite the fact that vaccination is the most effective way to control and prevent infectious diseases, the growing boom of the anti-vaccine movement has reduced the number of vaccinations and, therefore, represents a serious threat to public health. In this situation, this article analyses the most important ethical-legal aspects related to vaccination, and how they should be taken into account in order to configure the policies on the matter. Beside this, the public vaccination model that would best respond to the ethical problems of vaccination is presented, examining the way in which this model could be developed in the context of our Law.
Keywords: vaccination; public health; Ethics; herd immunity